AN ANALYSIS OF COMMUNICATION TYPES OF DEAF STUDENTS WITH ENVIRONMENT - Rahmah, Cipta Rizqi; Kholiq, Abdul (Jo-ELT (Journal of English Language Teaching)Fakultas Pendidikan Bahasa dan Seni Program Studi Pendidikan Bahasa Inggris, 2018)
The research aimed to analysis (1) the deaf student communicate with the deaf student; (2) with other disability; and (3) with normal people. This research used a qualitative approach. The sources of data are focusing on the communication types of deaf students by three deaf people SMALB Banjarmendalan Lamongan academic year 2016/2017. Data Collection Techniques are interview; observation; and documentation. Research Instruments in this study are a notebook to write about the interview; checklist paper; and field note. Analyzing technique in this study are organizing, coding and reducing, interpreting and representing. The result of this study are  Deaf children's communication with deaf children is more dominant using nonverbal rather than verbal. Use of continuous verbal communication such as Kinect (facial expression, eye contact, sign language), haptics, paralanguage, and proxemict. Deaf children communicate with other disability (down syndrome) is Deaf children's communication with dominant down syndrome children using nonverbal communication types. The use of intense verbal communication such as kinestict (facial expressions, eye contact, sign language) and haptics are two very important aspects of their communication. Deaf children's communication with normal people uses a combination of verbal (oral and writing) and nonverbal (kinect, haptic, and proxemic). Teachers will use a clear combination of sign language and oral. While researchers use oral, written and sign language to make it easier for deaf students to understand the conversation.